Improved practice in place of shifting cultivation and its effect on soil properties at Dipbu in Assam - Sarma, N N; Dey, J K; Sarma, D; Singha, D D; Bora, P; Sarma, R (The Indian Journal of Agricultural Sciences, 2012)
A field trial was conducted during 1988-89, 1989-90 and 1990-91 to study the effct of slash-and-burn practice (jhum) and subsequent intensive management on soil properties and to evaluate improved cultivation practices alternative to shifting cultivation. Four treatments of improved shifting cultivation and 2 traditional ones were studied on jhum land with 20% hill slope under rainfed condition. The treatments of improved cultivation comprised inclusion of improved varieties, application of manures and fertilizers, scientific crop planning by placing Horticultural crops in the border and field crops in tlte centre, sown across and along the slope, and the traditional ones with the without burning of surface litter for land clearing. The highest yield in terms of rice equivalent was recorded when pineapple [Ananascomosus (L.) Merr.], turmeric (Curcuma longa L.), ginger (Zingiber officinale Roscoe) and arum [Colocasia esculenta (L.) Schott) were grown in the border aad rice (Oryza sativaL.), maize (Zea mays L.), sesame (Sesamum indicum L.) and cotton (Gossypium spp) were sown across the slope in the centre under improved cultivation. Line sowing of rice, maize, sesame and cotton across the slope gave better result in terms of rice-equivalent yield than sowing along the slope. Burning of surface litter had no significant effect on yield and had insignificant effect on soil pH, organic matter, available N, P and K content, cation-exchange capacity and water-holding capacity of the soil. Available N, P and K status and organic matter content of the soil were depleted after successive 3 years of cropping in all the treatments. Improved cultivation practices arrested the degradation of organic matter, conserved the nutrients, increased the soil pH and soil environment, and sustained higher productivity.